The Implementation Of A Patient Safety Culture Is Crucial In Preventing Adverse Events In Healthcare Settings - Huwaina Af’idah; Nisrina Nisrina (International Journal of Medicine and Health, 2024)
The occurrence of patient accidents is like an iceberg phenomenon. Medical errors remain a global issue in the healthcare sector. The culture of safety aims to create safer patient care, considering that Adverse Events can not only increase healthcare service costs but also bring hospitals into a blaming area. This study aims to describe the patient safety culture at Melati Perbaungan General Hospital. This descriptive study observes the implementation of patient safety culture in preventing adverse events in the inpatient department at Melati Perbaungan General Hospital using a total sampling technique with criteria including human resources in the inpatient department, such as executors, responsible persons, and department heads, totaling 65 people. The measurement of patient safety culture uses the Hospital Survey on Patient Safety Culture (HSPSC) questionnaire with 12 dimensions of patient safety culture. The results show that the majority of respondents' characteristics in terms of age and length of work greatly support the creation of a patient safety culture, as most staff are in their productive age (31-40 years) and have an optimal working period (1-5 years) in performing their duties. The implementation of the patient safety culture by staff at Melati Perbaungan General Hospital is in the Positive Response category at 77.9%. This indicates that the patient safety culture has been well implemented.